2021
DOI: 10.1186/s13065-021-00772-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, energy and nutritional values, digestibility and functional properties of defatted flour, protein concentrates and isolates from Carbula marginella (Hemiptera: Pentatomidae) and Cirina butyrospermi (Lepidoptera: Saturniidae)

Abstract: Edible insects constitute a potential source of alternative proteins as a food supplement. The present study aimed to investigate the chemical composition, energy and nutritional values, the digestibility and functional properties of Carbula marginella (Thunberg) and Cirina butyrospermi (Vuillet) defatted flour, protein concentrates, and isolates. Carbula marginella has shown the highest content of protein (41.44%), lipid (51.92%), calcium (33.92 mg/100 g) and sodium (185.84 mg/100 g) while the highest content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
0
10
1
1
Order By: Relevance
“…As seen in Table 2 , with insect meals, most researchers use both phases (gastric and intestinal). However, some researchers have carried out simple gastric digestion [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ], and Séré et al [ 53 ] only performed enteric digestion. Only a few have previously added an oral phase [ 2 , 3 , 54 , 55 , 56 ].…”
Section: Methods Used For Digestion and For The Determination Of In V...mentioning
confidence: 99%
See 2 more Smart Citations
“…As seen in Table 2 , with insect meals, most researchers use both phases (gastric and intestinal). However, some researchers have carried out simple gastric digestion [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ], and Séré et al [ 53 ] only performed enteric digestion. Only a few have previously added an oral phase [ 2 , 3 , 54 , 55 , 56 ].…”
Section: Methods Used For Digestion and For The Determination Of In V...mentioning
confidence: 99%
“…This release causes a pH change (acidification) of the reaction medium, and a base must be added to maintain the pH. For the calculation of protein digestibility in the Hemiptera Carbula marginella and the Lepidoptera Cirina butyrospermi , Séré et al [ 53 ] used the following formula: Digestibility = 4.33 + 53.21X where X is the volume of NaOH (mL) poured at t = 10 min to maintain the pH at 8.0. Nielsen et al [ 68 ] indicated that the pH-stat technique should be used in pH conditions above 7, and Bryan and Classen [ 69 ] pointed out that this method is not suitable for determining food digestibility in terrestrial animals but is especially suitable for aquatic nutritional research.…”
Section: Methods Used For Digestion and For The Determination Of In V...mentioning
confidence: 99%
See 1 more Smart Citation
“…Threonine (9.90-10.47 g/100 g protein), leucine (8.43-9.44 g/100 g protein), and phenylalanine + tyrosine (6.22-8.92 g/100 g protein) were the predominant essential amino acids in defatted flour, protein concentrates and isolates of Macrotermes subhyalinus. Séré et al [44] reported a similar increase in leucine, isoleucine, and lysine content in the protein isolates of Carbula marginella and Cirina butyrospermi. Leucine and valine were limiting amino acids in defatted flour, protein concentrates, and isolates of Brachytrupes membranaceus, while lysine was a limiting amino acid in defatted flour of Macrotermes subhyalinus [45].…”
Section: Amino Acid Composition Of Brachytrupes Membranaceus and Macr...mentioning
confidence: 76%
“…Helium was used as carrier gas, injector split ratio 1:50, flow rate 1 mL/min. The FAs were individually identified and quantified using the chromatogram peak areas of previously calibrated external standards [ 39 , 40 ]. A methanolic stock solution (1000 mg L −1 ) of the standards (palmitic acid (16:0), stearic acid (18:0), oleic acid (18:1), linoleic acid (18:2), γ-linolenic acid (18:3), lauric acid (12:0), pentadecanoic acid (C15:0), eicosatrienoic acid (20:3), and erucic acid (22:1)) was available, and fresh dilutions for the working solutions were prepared daily ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%